How should a patient with rheumatoid arthritis behave after achievement of remission? - D. E. Karateev (Современная ревматология)
The paper considers the very urgent problem of optimization of the management of rheumatoid arthritis (RA) patients who have achieved remission (or persistent low disease activity) during therapy using biologicals. It analyzes the results of BeSt, OPTIMA, HIT HARD, ACT-RAY, AVERT, PRESERVE, RETRO, PRIZE, DRESS, HOPEFUL-2, and HONOR studies, the data of NinJa and CORRONA registries, and the experience gained in treating psoriasis concerning practically important issues, such as whether tumor necrosis factor-α inhibitors and biologicals with other mechanisms of action can be discontinued; whether the whole anti-inflammatory therapy can be stopped; whether the dose of biologicals can be reduced as an alternative to complete discontinuation or as a step to discontinue biologicals; whether repeated or intermittent therapy with biologicals can be used; what value of the depth of suppression of inflammatory activity is in solving the problem of whether biologicals can be discontinued. The current results may lead to the conclusion that in RA the dose of biologicals may be successfully reduced and, in some cases, the latter may be completely discontinued. This possibility seems to be associated with the depth of remission. Repeated use of biologicals generally gives rise to prompt improvement in patients with a recurrent disease-activity rebound. The results of a trial of etanercept are most optimistic. Re-treatment with biologicals generally provides fast improvement in patients with a relapse of disease activity. The results of the trials of etanercept are most optimistic.